The Volatility and Shock Transmission Patterns Between the BIST Sustainability and BIST 100 Indices - Baykut, Ender; Kula, Veysel (Frontiers in Applied Mathematics and Statistics, 2019)
This study aims at empirically investigating the volatility and shock transmission patterns between the BIST 100 Index and the relatively new BIST Sustainability Index, which is a platform for companies with high performance on the international sustainability criteria. Utilizing 678 daily data from 05/11/2014, the day the XSURD Index was launched, to 31/08/2017, the analysis employed a bivariate BEKK-GARCH (1,1) model. The findings indicate the existence of bidirectional volatility spillovers between two indices. Additionally, current volatility is affected by its past volatility for each index. As for the shock transmission, the BIST Sustainability Index is responsive to both its shocks and shocks arriving from the BIST 100 Index. However, the BIST 100 Index responds only to its shocks without any significant shock transmission from the BIST Sustainability Index.